A novel method for increasing biohydrogen production from food waste using electrodialysis. (7th June 2019) - Hassan, Gamal K.; Massanet-Nicolau, Jaime; Dinsdale, Richard; Jones, Rhys Jon; Abo-Aly, M.M.; El-Gohary, Fatma A.; Guwy, Alan
Abstract: The impact of continuous removal of volatile fatty acids on fermentative hydrogen production from food waste (FW) in a Continuously Stirred Tank Reactor (CSTR) was evaluated. Two experimental phases were conducted, a control phase and one in which volatile fatty acids were removed continuously from the reactor for the first time by electrodialysis (ED). Hydrogen yields were 64.7 cm 3 H2 /g VS and 227.3 cm 3 H2 /g VS for control phase, and ED phase respectively. Continuous removal of volatile fatty acids during fermentation not only increased H2 yields but increased the production of volatile fatty acids (a valuable chemical feedstock) from 0.14 g/g VS to 0.34 g/g VS. Highlights: A novel combination of anaerobic digestion and electrodialysis increased hydrogen production from food waste. Using electrodialysis increased hydrogen yield by factor of 3.5. Electrodialysis had an effect on the patterns of substrate utilization and volatile fatty acid production. Electrodialysis process is potentially compatible with 'real world' waste streams.